Amino acids production using pineapple plant stem by optimised one-step fermentation - Chu, Pei-Hsia; Jenol, Mohd Azwan; Phang, Lai-Yee; Ibrahim, Mohamad Faizal; Purkan, Purkan; Hadi, Sofijan; Abd-Aziz, Suraini (Springer Science and Business Media Deutschland GmbH, 2024)
Background: The surge in global pineapple production has led to an excess of waste, demanding a sustainable approach for bioconversion. Despite its substantial volume, pineapple plant stems remain largely neglected, often discarded as on-farm waste. These stems, composed of intricate structures, necessitate a multi-step process for effective bioconversion. A promising alternative involves a single-step approach using microorganisms to combine hydrolysis and fermentation processes, yielding significant amino acid production from pineapple plant stems. This is aligned with Sustainable Development Goals 13 in reducing carbon dioxide and greenhouse gas emissions from traditional waste disposal methods. Results: The utilisation of Bacillus subtilis ATCC 6051 for amino acid production demonstrated success, yielding 1.28 mg/mL of total free amino acids with a remarkable 67.13 mg/g yield. This represents a 13% increase in concentration and a 12% boost in yield compared to commercial starch. The study underscores the pivotal role of medium composition, highlighting the significance of pineapple plant stems as a substrate and other key components to enhance amino acid production. Conclusion: Notably, the study achieved a substantial improvement in total amino acids production, reaching 9.57 mg/mL with a yield of 423.97 mg/g—an impressive 6.32-fold increment. This emphasises the enhanced potential of pineapple plant stems as a valuable resource for amino acid production, shedding light on the importance of optimising medium composition for maximum yield.